Analisis Kinerja Multiple Pulse Position Modulation terhadap Interferensi Lampu Neon pada Sistem VLC - Naffisa Naufal Andriani; Akhmad Hambali; M. Irfan Maulana (Risenologi, 2021)
Visible Light Communication (VLC) technology is a wireless communication system that transmit information using the visible light spectrum. VLC has the advantage of not being affected by electromagnetic interference, but can be affected by interference from ambient light. There are two types of interference in the VLC system, namely natural interference from sunlight and ambient light interference from fluorescent or incandescent lamps. This study discusses the effect of fluorescent light interference on the VLC system using Multiple Pulse Position Modulation (MPPM) in a 10x10x3 meter room with Line Of Sight (LOS) channel. There are two scenarios carried out in this study discusses. The first scenario is the delivery of information using the VLC system without interference, while the second scenario is the delivery of information with interference from fluorescent lights. The final results of the simulations show that the VLC system in scenario I has a better performance compared to the VLC system in scenario II. This is evidenced by the results of the BER value obtained in scenario I with 2-PPM modulation obtained a value of 0.416, in 4-PPM modulation obtained a value of 0.335, and with 8-PPM modulation obtained a value of 0.231. In scenario II the BER value obtained with 2-PPM modulation is 0.466, in 4-PPM modulation is 0.432 and with 8-PPM modulation is 0.384. It also shows that 8-PPM modulation is the best modulation to transmit data compared to 2-PPM and 4-PPM modulation.